Analisis Lokasi Dan Jumlah Stasiun Pemadan Kebakaran Kota Pekanbaru - Jasriadi Jasriadi; Rian Trikomara Iriana; Sri Djuniati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Fire Company is an active protektif system in building structure. Pekanbaru is an area which is gristle to fire danger. Population of Pekanbaru City pertained is multitude, this affect to movement systems and development expanding everywhere. Location of effective post is an effort to minimize fire impact which possibly will happened. The research methodology consists of three phases: data collection, network analisys using network analyst extention, and discussion. Analyse optimation of station which have in Pekanbaru City conducted by using principle of service area to the stations which have been placed in one location. Service area in this study is defined as the minimum area that can be reached by fire station on the fire occur. Service area is generated using the network analisys extention in ArcGIS software. The results of this study indicate that stations still are not able to cover all of Pekanbaru areas. Station allocated by government in this time not enough served all region of Pekanbaru when at any times fire occur. On scenario 1-4 (existing station scenario with assumption speed of extinguisher car is 50-65 km/hour), stations cannot include all region of Pekanbaru. It means that Pekanbaru city still requires the addition of a new station building allocated to the areas not yet covered service area that is counted 5 (five) new stations.Keywords: optymal location, network analyst, service area , fire station